Systematic Literature Review: Implementation of Personality Development in Correctional Institutions - Silitonga, Christian Paruli; Kusmiyanti, Kusmiyanti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Personality development is a crucial component of the Indonesian correctional system, aiming to rehabilitate inmates so they can reintegrate into society and reduce recidivism rates. However, the high rate of recidivism and the issue of overcrowding in correctional institutions indicate a gap between policy formulation and program implementation. This study employed the Systematic Literature Review (SLR) method with the PRISMA approach to analyze 20 relevant national and international scientific articles. The analysis was based on George C. Edwards III’s policy implementation theory, which includes communication, resources, disposition, and bureaucratic structure variables. The findings revealed that the implementation of personality development programs in correctional facilities remains suboptimal due to limited professional staff, inadequate infrastructure, and inconsistent policy communication. Furthermore, programs such as religious development, intellectual development, legal awareness, national awareness, and physical health have not fully resulted in sustainable behavioral change. This study recommends strengthening human resource capacity, conducting data-based evaluations, and adjusting policies through a holistic rehabilitative approach to enhance the effectiveness of personality development programs in correctional institutions.